2007
DOI: 10.1177/0276146707302780
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Macro Linking Using System Dynamics Modeling: An Examination of Eco-Labeling Effects for Farmed Shrimp

Abstract: Eco-labeling has been heralded as a market-based approach useful in addressing environmental issues. While a growing number of eco-labeling projects are found in nations around the world, most models examining eco-labeling effects tend to be focused either on environmental impacts or consumer adoption of eco-labeled goods and do not attempt to link consumer behavior to environmental impact. The current article offers a somewhat different approach by using system dynamics modeling to capture both consumer adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Price premiums for ecocertifed shrimp produced under a tax and rebate policy could help cover the cost of implementing the policy. Arquitt and Cornwell (2005) apply system dynamics to examine the influence of eco-certification and labeling on shrimp aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…Price premiums for ecocertifed shrimp produced under a tax and rebate policy could help cover the cost of implementing the policy. Arquitt and Cornwell (2005) apply system dynamics to examine the influence of eco-certification and labeling on shrimp aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…This would address the question of the extent to which local origin induces a willingness to pay on the part of consumers. This is important because past research has suggested that individuals may not be willing to pay more unless they see personal advantages to the purchase (Arquitt and Cornwell 2007).…”
Section: Future Researchmentioning
confidence: 99%
“…Our meso-level approach responds to calls by researchers to link micro-level consumer behavior (Cornwell and Drennan 2004) with macro-level social and, in particular, environmental outcomes (Arquitt and Cornwell 2007). The impracticality of swaying hundreds of millions of individuals toward sustainable consumption has resulted in a new call to consider micro-meso-macro relationships (Layton 2008).…”
mentioning
confidence: 99%
“…Given the fact that system dynamics modelling has its roots in engineering, it has been commonly used in management‐related research because of its ability to handle both qualitative and quantitative variables and the interrelationships between these via the use of feedback structures (Galanakis, 2006). Additionally, the use of feedback structures equips KM researchers with the ability to link macro‐level system behaviour with micro‐level decision making in a complex social system (Sterman, 2000; Garud and Kumaraswamy, 2005; Arquitt and Cornwell, 2007). Furthermore, utilizing a formal mathematical model, such as a system dynamics model, allows researchers to identify themes common to the different textual descriptions and, in turn, enforces the internal consistency of the theory developed, whose core structures can be explicitly represented in the forms of graphs and models (Rudolph & Repenning, 2002).…”
Section: Resultsmentioning
confidence: 99%